Prevalence of comorbidities in Severe Acute Respiratory Syndrome in patients with COVID-19 and other infectious agentes (Research, Society and Development, 2020)
This study aimed to analyze the cases of acute respiratory syndrome - SARS caused by COVID-19, or not, in relation to the presence of heart diseases and diabetes, in severe cases in the State of Pernambuco, the Northeast region and in Brazil. Data were collected from the Ministry of Health's OpenDataSUS Database, covering information between 12/29/2019 and 9/14/2020. Analyzes were made with the rpart package of the R software, which builds classification or regression models that can be represented as binary trees. The results revealed a significant percentage of heart diseases and diabetes (average of 51% and 40%, respectively) present in patients with SARS, regardless of etiology, in the three areas considered. It was also observed that patients with heart disease develop SARS more frequently when affected with COVID-19 (64.6%) than with other etiologies (35.4%). The same was observed for diabetic patients with COVID-19 (67.1%) and for patients negative for COVID-19 (27.7%). The lethality rate was higher among patients with both comorbidities. It was 47.6% for diabetes; 45.3% for cardiac patients and 50.3% when in combination in patients affected by SARS caused by COVID-19. The results obtained are relevant to the development of public health measures seeking to identify patients at higher risk and to apply early and specific treatments in order to reduce mortality in these cases.